Slow Violence and the Echoes of Ecological Desecration in Imbolo Mbue’s How Beautiful We Were - OHAGWAM, Uchenna; ALBERT, Queen (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Slow violence is an idea developed by Rob Nixon. As an ecocritical concept, Nixon engages the gains of ecocriticism and postcolonial studies to make a unique blend of the conceptual resources of both theories in order to formulate a new framework suitable for reading, interpreting, and apprehending issues of environmental degradation, environmental humanities, environmental activism, and the environmental justice system. The paper engages Mikhail Bakhtin’s theory of narratology and the ecocritical theory and examines the idea of slow violence and its manifestations in How Beautiful We Were (2021), a novel by the Cameroonian-American writer, Imbolo Mbue. Mbue’s depiction of the exacerbating repercussions of capitalism wrought by oil extraction in the fictional tropical African village of Kosawa triggered this study. The novel is unique owing to the author’s ability to tell her story logically and in an engaging manner—through the development of a well-knit plot, realistic setting, true-to-life characters, the handling of conflict, and her skillful use of certain literary elements to achieve the theme of environmental dislocation in the novel. The paper therefore recommends that the appropriate deployment of the techniques of collective reportage, dialogism, in media res, juxtaposition of characters, holophrastic dictions, symbolism, metaphor, irony, and flashback can be applicable in the overall task of portraying a landscape of asphyxiating fumes, a desecrated ecosphere, and the image of the ironic contradictions of capitalist exploitation in contemporary time. The paper found that the use of the right narrative conventions can foster not just an understanding of the story line and plot development of a literary text but also the narrative’s preoccupation, and in the case of Mbue’s fiction, the theme of environmental injustice.